Răspunsuri la întrebare
Răspuns de
1
I=![\int\limits^0_1 {x e^{2x} } \, dx = \frac{1}{2} \int\limits^0_1 {2x e^{2x} } \, dx =- \int\limits^1_0( { e^{2x})' } \, dx = \int\limits^0_1 {x e^{2x} } \, dx = \frac{1}{2} \int\limits^0_1 {2x e^{2x} } \, dx =- \int\limits^1_0( { e^{2x})' } \, dx =](https://tex.z-dn.net/?f=+%5Cint%5Climits%5E0_1+%7Bx+e%5E%7B2x%7D+%7D+%5C%2C+dx+%3D+%5Cfrac%7B1%7D%7B2%7D++%5Cint%5Climits%5E0_1+%7B2x+e%5E%7B2x%7D+%7D+%5C%2C+dx+%3D-+%5Cint%5Climits%5E1_0%28+%7B+e%5E%7B2x%7D%29%27+%7D+%5C%2C+dx+%3D)
dela 0 la 1= e^1-e^0= e-1
c04f:
am pierdut un "-" deci este I= 1-e
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă